Strategi Pemerintah Kabupaten Gorontalo Tingkatkan Akuntabilitas Pengelolaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan - Salim, Alfiyah Agus; Tohopi, Rustam; Ramadhan, Nur Fazriyah (UIR Press, 2025)
This study examines Gorontalo Regency's plans for attaining the PBB-P2 revenue objective. This descriptive, qualitative research combines observation, interviews, and documentation to collect data, which is analysed using SWOT analysis. The results of the research that has been carried out are various strategies that have been implemented by the Government of Gorontalo Regency to continue to meet the regional original income target from the taxation sector, especially PBB-P2, which overall shows good results, but still experiences several obstacles, including uncertain community income, education related to PBB-P2 to the community is not comprehensive yet and has limnited human resources